The Dialectic of “Green” and “Retro”: A Case Study of Green Marketing Strategy Formulation Based on the Vision and Mission of Retrorika’s Owner - Akbar Amin; Alfina Jannah; Bhernanda Artino; Sudarmiatin Sudarmiatin; Ita Wilujeng (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Café retrorika is one of the cafes located in Batu City, Malang, which adopts a green marketing concept with a unique aesthetic touch, combining the concepts of “Retro” and “Eco-friendly”, where almost all of the café’s furniture and decorations are made from recycled materials, such as old windows, used motorcycle tanks, gas cylinders and rims, which are transformed into high-art decorative elements. Awareness of the importance of sustainable business is growing, including in the culinary sector. Cafes and restaurants now compete not only in terms of taste and service but also in their commitment to environmentally friendly concepts. Moreover, today’s consumers are increasingly selective in choosing places to eat that support local products, use environmentally friendly materials, and strive to reduce plastic waste. This is one of the reasons for building cafes with different concepts, as done by the owner and founder of Retrorika café. This study uses a qualitative approach with a case study research type. Data collection techniques include participant observation, interviews and documentation. The result show that Retrorika café was built based on the personal idealism of its owner as a green movement activist, rather than market calculations. The café’s “Retro” identity serves as physical evidence of sustainability practice through the use of used furniture while also creating a nostalgic experience. Its marketing strategy focuses on education through the Re-dukaci program, Retrorika goes to Halokes and Sa-Si-Su as an effort to prove the authenticity of green practices and mitigate greenwashing. These results can be concluded that the founder’s passion shapes the Green Corporate Identity and becomes a source of sustainable competitive advantage that is difficult to imitate.